2020
DOI: 10.7249/rra633-1
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Costs of Decarbonizing Costa Rica's Economy: Informing the Implementation of Costa Rica's National Decarbonization Plan Under Uncertainty

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license.Note that link provided above includes additional terms and conditions of the license. The opinions expressed in this publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It also allows estimating capacity expansion, generation production per type of power plant, generation costs per energy unit, number of jobs created per scenario, and GHG emission trajectory per power plant and fuel type. Estimations follow approaches similar to existing literature (Groves et al, 2020;Saget et al, 2020;Benavides et al, 2021;Quirós-Tortós et al, 2021;Solano-Rodríguez et al, 2021;Welsby et al, 2021;Arguello et al, 2022;Galindo et al, 2022;Kalra et al, 2023;Victor-Gallardo et al, 2024):…”
Section: Exploratory Model Of Expansion Pathways For the Electricity ...mentioning
confidence: 84%
See 1 more Smart Citation
“…It also allows estimating capacity expansion, generation production per type of power plant, generation costs per energy unit, number of jobs created per scenario, and GHG emission trajectory per power plant and fuel type. Estimations follow approaches similar to existing literature (Groves et al, 2020;Saget et al, 2020;Benavides et al, 2021;Quirós-Tortós et al, 2021;Solano-Rodríguez et al, 2021;Welsby et al, 2021;Arguello et al, 2022;Galindo et al, 2022;Kalra et al, 2023;Victor-Gallardo et al, 2024):…”
Section: Exploratory Model Of Expansion Pathways For the Electricity ...mentioning
confidence: 84%
“…In this context, countries like Costa Rica, Peru, Chile, and Colombia have actively examined the cost-benefit aspects of decarbonizing their economies (Groves et al, 2020;Benavides et al, 2021;Quirós-Tortós et al, 2021;Arguello et al, 2022), a trend that the Dominican Republic closely follows. These studies have shown that decarbonization offers substantial economic opportunities for Latin American countries.…”
Section: Introductionmentioning
confidence: 99%
“…See the Box with 'Facts on pineapple residues in Costa Rica' as developed in this study. The amount of biogas that potentially can be produced as part of PALF valorization is considerable and contributes to Costa Rica's goal of net-zero emissions by 2050 (Groves et al, 2020).…”
Section: Enabling Environmentmentioning
confidence: 99%
“…Least-cost is also often built into regulatory requirements such as those informed by the U.S. government estimates of the social cost of carbon. As one example, a recent, large-scale DMDU study of Costa Rica's National Decarbonization Plan was generally communicated to senior decision makers and the public in cost terms because this was the language they were most comfortable hearing (Groves et al, 2020).…”
Section: Unige Riskmeter Available Online At: Wwwriskmeterchmentioning
confidence: 99%